2015
DOI: 10.3391/mbi.2015.6.1.02
|View full text |Cite
|
Sign up to set email alerts
|

A vector analysis of marine ornamental species in California

Abstract: The occurrence of problematic pest organisms is an increasing global phenomenon, adversely affecting a range of environments and associated values. In marine systems, the efficacy of pest control has to date been constrained by a lack of tools that are not only highly effective, but also applicable across broad spatial scales. Here we consider the extent to which biological control (biocontrol) has the potential to fulfil these needs. We describe different biocontrol approaches and potential ecological mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
1
9
0
2
Order By: Relevance
“…Many online retailers advertise and presumably sell a diverse stock list of Pteroinae directly to the public, but that diversity was not apparent in our retail survey results. For California, Williams et al [37] reported the online availability of 12 species to hobbyists from internet sources. At the retail level, our survey found only six species available in 10 coastal states, only five of which were found in 50 Californian retail stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many online retailers advertise and presumably sell a diverse stock list of Pteroinae directly to the public, but that diversity was not apparent in our retail survey results. For California, Williams et al [37] reported the online availability of 12 species to hobbyists from internet sources. At the retail level, our survey found only six species available in 10 coastal states, only five of which were found in 50 Californian retail stores.…”
Section: Discussionmentioning
confidence: 99%
“…California was included because P . volitans has a thermal niche that may allow for permanent established populations in some areas of southern California [36], and because it is a major hub for the marine ornamental fish trade [37]. Retail stores were identified and selected using a standardized Google search for the term “saltwater aquarium store in” followed by the state where that store is located.…”
Section: Methodsmentioning
confidence: 99%
“…En la actualidad solo hay dos regiones tropicales del mundo donde Pterois volitans/miles no ha sido capaz de irrumpir: la costa occidental de África y el Pacífico oriental tropical (Schofield, 2010). Esta última abarca desde el golfo de California (GC; México) hasta el norte de Perú, y en ella el pez no se ha establecido a pesar de la presencia de arrecifes coralinos y rocosos (Glynn et al 2017) que son hábitats propicios para la colonización, por lo que, dada la afinidad de hábitat, Williams et al (2015) manifestaron preocupación sobre los efectos de la llegada de Pterois spp. a la costa oeste de los Estados Unidos.…”
Section: Introductionunclassified
“…Global transportation networks have resulted in large numbers of non-indigenous species (NIS) appearing in marine ecosystems. Major vectors of introduction include the aquarium and ornamental trades (Williams et al 2015, Vranken et al 2018, ballast water (Carlton and Geller 1993), biofouling on commercial ships (Williams et al 2013, Lacoursière-Roussel et al 2016, Whitman Miller et al 2018, transport with shellfish (Hégaret et al 2008), and transoceanic transport after natural disasters (Carlton et al 2018, Hanyuda et al 2018. A common invader is Grateloupia turuturu Yamada, a low to subtidal red alga originally described from Japan (Yamada 1941) that now has a nearly global distribution after primary and secondary introductions (e.g.…”
Section: Introductionmentioning
confidence: 99%